ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR PENILAIAN KINERJA KEUANGAN (STUDI KASUS KOPERASI SIMPAN PINJAM CU DAMAI SEJAHTERA) - Tamba, Nanci Octavianiman; Putra Hrp, Ardhansyah (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
The objective to be achieved from this research is to find out how financial performance is assessed using financial reports carried out by the CU Damai Sejahtera Savings and Loans Cooperative. The aim to be achieved from this research is to find out how financial performance is assessed using financial reports carried out. This research uses quantitative research methods. Quantitative research methods are methods that use number calculations which will later be used to make decisions in solving a problem. Here, researchers use quantitative research methods because this research explores the phenomenon of Financial Report Analysis as a Basis for Financial Performance Assessment (Case Study: CU Damai Sejahtera Savings and Loans Cooperative). In taking this research, researchers used the Saturated Sampling Technique. Saturated sampling technique is a sampling technique that uses all members of the population as samples. Therefore, this research uses the entire population as a sample, namely the financial reports of the CU Damai Sejahtera Savings and Loans Cooperative for 3 years, namely 2020-2022. Based on research results in 2020, the financial performance of the CU Damai Sejahtera Savings and Loans Cooperative based on the Return On Assets (ROA) ratio in 2020-2022 is quite healthy. Based on the Net Profit Margin (NPM) ratio, the financial performance of the CU Damai Sejahtera Savings and Loans Cooperative in 2020-2021 shows healthy criteria and in 2022 shows very healthy criteria. Based on the Return On Equity (ROE) ratio, the financial performance of the CU Damai Sejahtera Savings and Loans Cooperative in 2020-2022 shows fairly healthy criteria.